Efektivitas Kinerja Pemerintah Desa dalam Merealisasikan Program-program Pembangunan Desa (Studi Tentang Program Cetak Lahan Sawah di Desa Jiwa Baru Kecamatan Lubai Kabupaten Muara Enim) - Kurota Akyuni Mawadda; Eko Budi Sulistio; Apandi Apandi (Jurnal Administrativa, 2023)
The Rice Paddy Print Program is a village program arranged by the Jiwa Baru Village Government which aims to maximize the use of untouched land into productive land and also to turn Jiwa Baru Village as a rice-producing village in Lubai District. This study aims to describe the effectiveness of the Village Government's performance in realizing the village development programs through the implementation of the rice paddy printing program in Jiwa Baru Village, Lubai District, Muara Enim Regency. The type of research used in this study is a descriptive qualitative research. The data was collected by means of observations, interviews and documentation of informants who were directly involved in this activity. The result of this study indicates that the performance of the Jiwa Baru Village Government in implementing the rice paddy printing program has been run effectively in accordance with the performance effectiveness measurement criteria, namely the target approach where the performance effectiveness highly focuses on results. Apparently, the program output is quite good, as evidenced by the realization of the rice paddy print in Jiwa Baru Village, and so likely the program outcome which has also been good due to the increasing participation of the community and the conditions of fulfilled food needs for them, especially the increasing of rice production in Jiwa Baru Village. This Rice Paddy printing program offers a positive impact for the community, farmers and also the Jiwa Baru Village Government. However, this rice paddy printing program still has some problems in terms of providing facilities and infrastructures.